Costs and emissions: Comparing electric and petrol-powered cars in New Zealand. (January 2021) - Hasan, Md Arif; Frame, David J.; Chapman, Ralph; Archie, Kelli M.
Highlights: Used electric vehicles are now the most cost competitive among all vehicle types. New electric vehicles are the least cost competitive across all scenarios. A decrease in electricity prices and discount rates would make EVs less costly to use. Replacing an ICEV by an EV could in principle reduce emissions by 87–90%. Abstract: In New Zealand, the average age of a light vehicle in 2018 was 14.09 years. Despite having an old light vehicle fleet, no study has been conducted so far to calculate the per-kilometre cost of ownership (PCO) for old used cars. Therefore, this study attempts to identify the PCO of a new and a used light duty EV and light duty petrol-powered car over a 12-year period. The emissions reduction potential of EVs is also investigated. Findings are that the PCO for a used EV is the lowest (25.5 NZ cents) followed by the PCO for a used petrol-powered car (31.5 NZ cents). Most importantly, replacing a light petrol-powered ICEV by a light EV can reduce GHG emissions at the user level by 90% if New Zealand could maintain its low emission grid electricity. The findings have policy implications for countries that are considering rapid emissions reduction through EVs.